2003
DOI: 10.3368/aoj.53.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Can the Brückner Test be Used as a Rapid Screening Test to Detect Amblyogenic Factors in Developing Countries?

Abstract: Although imperfect, the Brückner test may be a low cost alternative to either screening with photo screener or to no screening for amblyogenic factors in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Photorefraction devices capture images of the light crescent generated on the pupillary red reflex. Results have been comparable to the Brückner test [23,27]. However, unlike the Brückner test, which relies on a live, moving subject, photoscreener images permit an unlimited amount of time for interpretation [20].…”
Section: Photoscreenersmentioning
confidence: 65%
“…Photorefraction devices capture images of the light crescent generated on the pupillary red reflex. Results have been comparable to the Brückner test [23,27]. However, unlike the Brückner test, which relies on a live, moving subject, photoscreener images permit an unlimited amount of time for interpretation [20].…”
Section: Photoscreenersmentioning
confidence: 65%
“…The idea to screen for ocular morbidities using Bruckner’s reflex is not new and various studies have attempted to study its efficacy [ 19 , 20 , 21 ]. Photographic analysis of Bruckner’s reflex was attempted by Kakkinen K et al way back in 1981 [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…84.1%. [7] Amitava evaluating the modified Brückner test (MBT) using the streak retinoscope,[5] (on children who failed 6/9 Snellen) has reported the sensitivity and specificity as follows: 57% and 97% for anisometropia of 0.5 D; 74% and 95% for anisometropia of 1 D, and 50% and 98% for strabismus and concluded that MBT is accurate and useful for ruling them. Considering the high specificity obtained in our study, it is likely that the CDC method is equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Such advantages accrue by utilizing the Bruckner's reflex, with the retinoscope and the consumer digital cameras (CDC). [5678] The enhanced Bruckner reflex, visible from the top or side of the ophthalmoscope,[9] generates a light crescent in the pupil of an ametropic eye, while an uniformly brighter reflex is seen from the strabismic eye. The child friendly CDC records this, permitting both anisometropia and strabismus to be identified.…”
Section: Introductionmentioning
confidence: 99%